Valve and transistor audio amplifiers - Hood, John Linsley (Newnes, 1997)
The audio amplifier is at the heart of audio design. Its performance determines largely the performance of any audio system. John Linsley Hood is widely regarded as the finest audio designer around, and pioneered design in the post-valve era. His mastery of audio technology extends from valves to the latest techniques. This is John Linsley Hood's greatest work yet, describing the milestones that have marked the development of audio amplifiers since the earliest days to the latest systems. Including classic amps with valves at their heart and exciting new designs using the latest components, this book is the complete world guide to audio amp design. John Linsley Hood is responsible for numerous amplifier designs that have led the way to better sound, and has also kept up a commentary on developments in audio in magazines such as The Gramophone, Electronics in Action and Electronics and Wireless World. He is also the author of The Art of Linear Electronics and Audio Electronics published by Newnes. Complete world guide to audio amp design written by world famous author Covers classic amps to new designs using latest components includes the best of valves as well as best of transistors.